Exploring the Differential Effects of Perceived Threat on Attitudes Toward Ethnic Minority Groups in Germany - Jedinger, Alexander; Eisentraut, Marcus (Frontiers in Psychology, 2020)
Adopting a differentiated threat approach, we investigated the relationship between cultural, economic, and criminal threat on attitudes toward four different ethnic minorities in Germany (Muslims, foreigners, refugees, and Sinti and Roma). We hypothesized that the effect of different types of intergroup threats on ethnic prejudice varies with the perceived characteristics of minority groups. Using a representative sample of German adults, we found that cultural and economic threat primarily predicted attitudes toward Muslims and foreigners, while criminal threat played a minor role in attitude formation among the majority population. For refugees and Sinti and Roma, all three types of intergroup threats were found to be equally important for the prediction of attitudes toward these minority groups. These results are only partially in line with the culture-specific threat profiles of these minority groups in the German context. Therefore, we discuss the tenability of the differentiated threat approach to explain the genesis of ethnic prejudice in different cultural contexts.